Analisis E-Commerce Terhadap Keputusan Pembelian Produk Olahan Tape Di Kabupaten Jember - Trias Setyowati; Fefi Nurdiana Widjayanti (Universitas Muhammadiyah Jember, 2021)
The Covid-19 pandemic has created conditions of uncertainty that have led to a global economic recession in 2020. E-Commerce as an option is used as a business support. The purpose of this study was to determine and analyze whether the trust, convenience, price, and quality of information influence consumer decisions to purchase online tape products in Jember Regency. The data used are quantitative data which are classified into certain categories using tables to facilitate analysis of the SPSS version 23 program. To measure the perceptions of the respondents who have been collected, a Likert scale is used. Based on data analysis using multiple linear regression that trust has a positive but insignificant effect on purchasing decisions for processed tape products, while convenience, price and quality of information have a positive and significant effect individually on purchasing decisions for processed tape products. And simultaneously trust, convenience, price and quality of information have a positive and significant effect on purchasing decisions for tape processed products.